Student Experience In Clinical Practice Model Preceptorship In Stikes Hang Tuah Surabaya - Imroatul Farida; Setiadi Setiadi; Ferlinda Putri Heviyanti (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2025)
Introduction: Preceptorship is a clinical teaching model in nursing that serves as a strategic approach to enhance nursing students' competencies. This model aims to develop students into professional nurses who are knowledgeable, responsible, and capable of improving the quality of nursing services in clinical settings. Objectives: The study aimed to describe the experiences of nursing students during clinical practice using the preceptorship model at a hospital in Surabaya, Indonesia. Methods: This descriptive study involved nursing students in their final academic year. A total population of 81 students was included using probability sampling with a simple random sampling technique. Data were collected through a structured questionnaire and analyzed descriptively. Results: The study found that 77 students (95.1%) actively participated in clinical practice, 62 students (76.5%) were able to manage cases independently, 74 students (91.4%) demonstrated the ability to apply clinical knowledge and skills, and 71 students (87.7%) were able to interact effectively with their preceptors. Conclusions: The preceptorship model enabled students to be fully engaged in learning and healthcare service delivery, increased their confidence in case management, and allowed them to integrate theoretical knowledge into real clinical situations. Positive interaction with preceptors significantly supported students’ development of clinical skills and professional competence.